Design and analysis of wheelchair in term of daily usage - Ahmad Muhaimin, Ismail (2012)
Manual wheelchair propulsion in daily life is increasing day to day. So, preliminary study of human factors engineering is important in designing the wheelchair to be more ergonomics for them in doing daily activities. The main objective of this project is to improve the existing wheelchair in term of daily usage. It is focus on the use of simulation in analyzing the critical parts of the wheelchair model and evaluates it in term of daily usage. Evaluate the critical part of stress on the wheelchair which consists of seating support and wheel caster. In this steps, applying the knowledge gathered from the questionnaire is use to make a design refers to case data that suitable for the project. Several sketches were made and only three were selected based on suitability of the design. Three sketches being draw into SolidWorks software and then go through to simulation process by using FEA tools that is ALGOR software, the three designs was analyzed using constant force with three different materials. From the analysis, the Stress Von Misses was used to calculated safety factor. The result showed that, design 3 have highest value of safety factor with material E-Glass fiber which is 2.77, followed by Steel ASTM A36 is 2.44 on design 3 and 1.95 on design 2 with material E-Glass fiber. The highest number of safety factor is E-glass Fiber on design 3. So, the best selection of material is E-Glass Fiber for the Design 3.